CONCEPTUAL BLENDING THEORY IN THE FORMATION OF PROVERB’S MEANING ACCORDING TO ANDERSSON’S COGNITIVE MODEL - Abosh, Nizar; Ahmad, Shoreshvan (Humanities Journal of University of Zakho, 2025)
Cognitive linguistics is considered as a contemporary branch of linguistics that has drawn considerable attention among modern linguists. Through a cognitive lens, this discipline examines language, raising questions about linguistic phenomena from this perspective. Akin to their counterparts in other linguistic domains, cognitive linguists regard language as a central subject and aim to analyze both the system and function of language from the standpoint of the mind. Among the primary objectives of cognitive linguistics is to elucidate the processes occurring within the human mind, especially the way information is received, and meanings are constructed. In cognitive linguistics, some scholars consider conceptual blending theory to serve as a complement to mental spaces theory and the broader cognitive domains of intelligence. Although conceptual blending theory is also complicatedly linked to conceptual metaphor theory, it was specifically formulated to tackle challenges that neither mental spaces theory nor conceptual metaphor theory could adequately resolve. With the aim of clarifying how meaning is formed in certain expressions within the Kurdish Language, this research investigates Andersson’s cognitive model for understanding Proverb’s. Drawing upon the foundational principles of this model, the study addresses the mechanisms by which meaning is constructed internally, demonstrating how Proverb’s can involve complex relationship between different mental domains, ultimately leading to the emergence of a new, uniquely characterized conceptual space. Within the framework of conceptual blending theory, Andersson’s cognitive model provides partial insight into the way such proverbs are generated, employed, and interpreted. The present study attempts to answer the following central question: To what extent can this model be used to analyze the formation of novel meanings in Proverb’s, and how valid or reliable is this approach? The primary aim of this research is to enable more precise analysis and explanation of Proverb’s through a new model of meaning formation, while providing improved explanations and new interpretations in language.